Determining of process parameters of the PLA/titanium dioxide/hydroxyapatite filament - Olam, Mikail (Taylor & Francis Ltd, 2022)
In this study, filaments for FDM 3D printers were produced by extrusion method by mixing 95% polylactic acid (PLA), 1% hydroxyapatite ( HA) and 4% titanium dioxide (TiO2). The extruder temperature, raster angle and layer thickness parameters, and printing defects of the prints made with the FDM 3D printer were examined. According to the dimensional analysis, 0.5-2% dimensional deviations occurred in 3D prints. The least average roughness value was 12.1 mu m on the Z-axis surface, the highest average roughness value was 14.6 mu m on the Y-axis surface. The highest ultimate tensile strength was 57 MPa at the layer thickness of 0.15 mm, extruder temperature of 205 degrees C and raster orientation of 45 degrees. The highest modulus of elasticity was 2020 MPa at the layer thickness of 0.15 mm, extruder temperature of 220 degrees C and raster orientation of 45 degrees. The highest elongation at break was 2.0 mm at the layer thickness of 0.20 mm, extruder temperature of 220 degrees C and raster orientation of 45 degrees. The dimensional deviations in the X, Y and Z axes plane were approximately 1%. X parallelism, Y parallelism and Z profile surface values were approximately 0.6%.
Keywords: PLA; titanium dioxide; hydroxyapatite; raster orientation; layer thickness; extruder temperature; average roughness